Symbioses of Ciliates (Ciliophora) and Diatoms (Bacillariophyceae): Taxonomy and Host–Symbiont Interactions - Fernando Gómez (Oceans, 2020)
The nature of the plankton symbioses between ciliates and diatoms has been investigated from the tropical South Atlantic Ocean, and Mediterranean and Caribbean Seas. The obligate symbioses of the diatoms Chaetoceros dadayi or C. tetrastichon with the tintinnid Eutintinnus spp., and Chaetoceros coarctatus with the peritrich ciliate Vorticella oceanica are the most widespread, and the consortium of Chaetoceros densus and Vorticella sp. have been rediscovered. Facultative symbioses between Eutintinnus lususundae and Chaetoceros peruvianus, Hemiaulus spp., and Thalassionema sp. are less frequent, often containing three or four partners because Hemiaulus can also harbor the diazotrophic cyanobacteria Richelia intracellularis. Another three-partner consortium is the peritrich ciliate Zoothamnium pelagicum, ectobiont bacteria, and the diatom Licmophora sp. The predominantly oligotrophic conditions of tropical seas do not favor the survival of large diatoms, but large species of Coscinodiscus and Palmerina in facultative symbiosis with Pseudovorticella coscinodisci have a competitive advantage over other diatoms (i.e., reduction of sinking speed and diffusive boundary layer). Symbioses allow sessile peritric ciliates to extend their distribution in the pelagic environment, permit boreal-polar related diatoms such as C. coarctatus or Fragilariopsis doliolus to inhabit tropical seas, and help large diatoms to extend their survival under unfavorable conditions.